ON THE ISSUE OF STUDYING RUSSIAN REALITIES IN AN AUDIENCE WITH AN UZBEK LANGUAGE OF INSTRUCTION (World Bulletin of Social Sciences, 2024)
This article is about revealing the meaning of ethnocultural realities by translational and non-translational methods. The author refers to the translation method of semantics as translation-interpretation, in which, in addition to the equivalent in their native language, students are informed about the coincidence or discrepancy in the scope of the meaning of lacunae. We are also talking about a non-translational method of semantics, which includes: demonstration of objects, gestures, actions, paintings, drawings, slides, slides and disclosure of the meanings of realities in Russian, for which definitions can be used - descriptions of the meaning of a new word with already known words
Keywords: reality; realitysemantics; visibility